Yield forecasting of rice and wheat crops for eastern Uttar Pradesh - R. S. SINGH; CHANDRABHAN PATEL; M. K. YADAV; K.K. SINGH (Journal of Agrometeorology, 2014)
Eighteen years (1991-2008) of weather data and yield data of rice and wheat for 9 districts of Eastern Uttar Pradesh was used to develop yield prediction equations. Models were validated with 2 years (2009 and 2010) data. Results indicated that models explained 51 to 79 percent variations for rice yield and 65 to 92 percent variations for wheat yield in different districts. The percent Mean Bias Error (MBE) was between -1.05 (Mau) to 6.17 (Mirzapur) for rice and from -6.56 (Mau) to 0.01 (Varanasi) for wheat crop. The percent Root Mean Square Error (RMSE) was between 6.87 (Jaunpur) to 11.60 (Sant Ravidas Nagar) for rice and from 5.52 (Mirzapur) to 11.11 (Mau) for wheat crop. This revealed that the models can be used to some extent for predicting the yield in different districts of Eastern Uttar Pradesh.